Interação do hidrogênio com a microestrutura da liga de alta entropia Fe38Mn25Ni24Co5Cr2Al4Ti2 endurecível por precipitação - Marques, Sara Corrêa (2018)
In the context of overcoming the requirements for materials with exceptional properties, a new class of alloys is being studied. High entropy alloys were defined as solid solution alloys that contain multiple principal elements. The concept of high entropy alloys introduces a new path of developing advanced materials with unique properties. The possibility to promote the precipitation hardening mechanism in high entropy alloys means an important gain in mechanical performance. Nowadays, there is a great effort in producing metallic alloys with high mechanical resistance associated with high resistance to corrosion and to hydrogen embrittlement. It is in this context that the present work fits. The interaction between hydrogen and the microstructure of the precipitationhardened high entropy alloy Fe38Mn25Ni24Co5Cr2Al4Ti2 was investigated in the present work. The alloy was experimentally fabricated and, subsequently, thermo-mechanically processed. Computer simulation via Thermo-Calc® was used to aid the determination of the composition. Several analyses were conducted, including X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM) e mechanical tests. The study of the hydrogen interaction with the alloy was analyzed by gaseous permeation tests e tensile tests in hydrogenated samples. The improvement of mechanical properties by precipitation hardening was observed by analyzing the tensile tests. Low hydrogen diffusivity was observed at the alloy in the homogenized and precipitated states, comparable to duplex stainless steels and inconels. The experimental results obtained in the present work demonstrate the promising properties of the fabricated alloy for severe applications.